Crohn's disease with respiratory tract involvement. Issue 12 (December 1987) - Lemann, M; Messing, B; D'Agay, F; Modigliani, R
Abstract : Symptomatic respiratory tract involvement with granulomatous bronchial lesions has not yet been described in Crohn's disease. We report two patients with colonic Crohn's disease and severe respiratory symptoms (dyspnoea associated in one of the patients with voicelessness); erythema, aphthoid and superficial ulcerations were found in the colon and whitish granulations in the bronchi at endoscopy. Non-caseating tuberculoid granulomas were found in the colonic mucosa of both patients, as well as in the bronchial mucosa of one of them; in the second a diffuse inflammatory infiltrate including epithelioid cells was found underneath an erosion of bronchial epithelium. Both patients improved on oral prednisone. These two patients probably had bronchial involvement by Crohn's disease.